Pengabdian Masyarakat dengan Meningkatkan Minat Belajar pada Anak SDN 02 Babakanraden Melalui Metode Pembelajaran Kuis Interaktif - Yuaniko Paramitra; Dhistianti Mei Rahmawantari; Jeremy Jordan; Muhammad Fauzi; Ryan Hotmaruli; Tatag Herbayu (Abdimas Universal, 2023)
Community service is intended so that childrens can be independent in everyday learning and can increase their interest in learning. The methods used are: 1) learning assistance, 2) quiz, 3) test/practice questions, and 4) interaction/question and answer. The results of this activity shows that children are comfortable, increasing their intention to study and happy when learning, both with learning materials, subjects,  or with quiz interactive learning methods.